1975
DOI: 10.1055/s-0028-1093717
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Exocrine Pancreatic Secretory Process by Insulin In Vivo

Abstract: The three major phases in the secretory process in the exocrine pancreas (synthesis, intracellular transport, zymogen discharge) have been tested in vitro after changing circulating insulin levels in rats in vivo. One group of rats received a continuous infusion of glucose for periods up to 72 hours, which keeps blood glucose levels above 200 mg/100 ml and immunoreactive insulin (IRI) raised to 130 muU/ml. As a result of this treatment, amylase content in the pancreas increases by 25% while chymotrypsinogen an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
41
1
2

Year Published

1976
1976
2002
2002

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(51 citation statements)
references
References 8 publications
7
41
1
2
Order By: Relevance
“…Lack of endogenous insulin has been suggested as causing the atrophy of the pancreas in chronic Type 1 diabetes [12,[29][30][31], as insulin has been shown to promote growth and protein synthesis of the acinar cells [11][12][13]30]. This conclusion is substantiated by clinical studies on the exocrine secretory capacity of the pancreas in chronic Type I diabetes demonstrating decreased secretion of enzymes [32][33][34][35][36].…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Lack of endogenous insulin has been suggested as causing the atrophy of the pancreas in chronic Type 1 diabetes [12,[29][30][31], as insulin has been shown to promote growth and protein synthesis of the acinar cells [11][12][13]30]. This conclusion is substantiated by clinical studies on the exocrine secretory capacity of the pancreas in chronic Type I diabetes demonstrating decreased secretion of enzymes [32][33][34][35][36].…”
Section: Discussionsupporting
confidence: 64%
“…The pancreatic atrophy is attributed to the lacking trophic effect of insulin on the acinar cells [2,3,[9][10][11][12][13]. The extent of the exocrine atrophy, however, appears to vary considerably from patient to patient and has not yet been related to the remaining insulin positivity in the pancreas, to diabetes duration or to the degree of microangiopathy.…”
mentioning
confidence: 99%
“…They concluded that insulin played a key role in the regulation of amylase synthesis. Adler and Kern (1975) supported them by their experiments of alloxan diabetic rats. They considered that insulin affected directly the protein synthesis and amylase secretion of the exocrine pancreas in normal rats, while in chronic alloxan diabetic rats for a duration of 9 months the alteration of the exocrine pancreatic function depended on the severity of the diabetes and was related to the decrease of circulating plasma insulin levels.…”
Section: Discussionsupporting
confidence: 48%
“…Amylase secretion from exocrine pancreas decreases in insulin dependent diabetics as well as in alloxan or streptozotocin diabetic animals (Chey et al 1963;Vacca et al 1964;Bock et al 1967;Palla et al 1968;Soling and Unger 1972;Imamura 1976). Adler and Kern (1975) reported that the decrease of amylase secretion in alloxan diabetic rats was closely related with a decrease in serum immunoreactive insulin.…”
mentioning
confidence: 99%
“…The effect may be mediated by increased blood glucose levels (Nakajima & Magee, 1970), insulin release from the pancreas and its effect on the biosynthesis of amylase (Abdeljlil, Palla & Desnuelle, 1965;Soling & Unger, 1972;Adler & Kern, 1975) well known protein catabolic action of glucagon (Miller, 1965), lowering of serum calcium with concomitant hyperglycemia (Paloyan, Paloyan & Harper, 1967), competitive inhibition of pancreozymin (and related peptides, for example, caerulein, Dyck et al 1969;Glasser et al 1972;Konturek et al 1974) or secretin (Dyck et at . 1969;Nakajima & Magee, 1970).…”
Section: Discussionmentioning
confidence: 99%